Chapter Le dinamiche del mecenatismo signorile negli spazi sacri: un percorso per riconsiderare le geografie e le gerarchie del patronage artistico in Italia? - Rossetti, Edoardo (Reti Medievali E-Book, 2023)
The paper aims to outline some of the strategies of aristocratic patronage in sacred spaces in the Italian peninsula. The commissioning of elaborate marble funerary monuments, the choice of location for chaplaincies or entire churches, convents and monasteries, and the choice of the religious order to which to entrust them are indicated here as keys to understanding the internal distinctions within the Italian aristocracies. In particular, a new examination of aristocratic patronage between the 14th and 16th centuries is considered a means to address a general revision of the Italian cultural hierarchies and geographies of Vasari's legacy.